Economywide impact of maize export bans on agricultural growth and household welfare in Tanzania: A dynamic Computable General Equilibrium model analysis - Diao, Xinshen; Kennedy, Adam (Wiley, 2016)
Export bans have been frequently used by developing countries in recent years in an attempt to ensure domestic food supplies and insulate domestic market prices from international price hikes. This article uses Tanzania to examine the impact of export bans using a computable general equilibrium model. We find that banning cross‐border maize exports has very little effect on the national food price index and that the benefits from lower maize prices are captured primarily by urban households, while maize producer prices decrease significantly. The export ban further decreases the wage rate for low‐skilled labour and the returns to land, while returns to non‐agricultural capital and wage rates for skilled labour increase, further hurting poor rural households and thus increasing poverty for the country as a whole.